MI H2 2021 Prelim P1 Solution
MI H2 2021 Prelim P1 Solution
MI H2 2021 Prelim P1 Solution
Qn Solution
1(i) d 1 d
( 4 − x2 )
−1
[1] = 2
dx 4 − x dx
2x
=
( 4 − x2 )
2
1(ii) ⌠ x2
[4] dx 1 dv 2x
⌡ (4 − x )
2 2 Let u = x, =
2 dx ( 4 − x 2 )2
⌠
1 2x du 1 1
= x dx = , v=
2 (4 − x )
2
2 dx 2 4 − x2
⌡
1 1 ⌠ 1 1
= x 2
− 2
dx
2 4 − x ⌡ 2 4 − x
x 1 1
= − ⌠ dx
2(4 − x ) 2 ⌡ 4 − x
2 2
x 1 1 2+ x
=2 − ln +c
2 ( 4 − x ) 2 2 ( 2 ) 2 − x
x 1 2+ x
= − ln +c
2 ( x + 4) 8 2 − x
2
Qn Solution
2(a) ( 0, b ) → ( 0, 0 )
translate b units in negaive y direction
(i)
[1]
Note: ( a, 0 ) → ( a, −b ) ( not required )
2(ii) scale parallel to x axis by scale factor
1
[1] ( a, 0 ) →
a
(1, 0 )
1
scale parallel to x axis by scale factor
( 0, b ) → a
( 0, b )
2(b) Range of g = ( −∞,3) ∪ ( 3, ∞ ) or \ {3}
(i)
[2] Domain of h = ( −∞, ∞ )
Since range of g ⊆ domain of h
⇒ hg exists
2(b) 1 1
(ii) hg ( x ) =2 − 3 − =−1 +
x −1 x −1
[3]
Qn Solution
Method 1
( hg ) ( 3) = a
−1
hg ( ( hg ) ( 3) ) = hg ( a )
−1
1
3 =−1 +
a −1
1
=4
a −1
5
a=
4
-------------------------------------------------------
Method 2
To find ( hg )
−1
Let
1
y =−1 +
x −1
1
y +1 =
x −1
1
x −1 =
y +1
1
=x +1
y +1
1
( hg ) = ( x)
−1
+1
x +1
1 5
( hg ) ( 3=)
−1
1
+=
3 +1 4
Qn Solution
3(i) dy du
[3] y = ux3 ⇒ = x3 + 3ux 2
dx dx
du
x 2 x3 + 3ux 2 − 3 x ( ux 3 ) + 4 =0
dx
du
x5 + 3ux 4 − 3ux 4 + 4 = 0
dx
du
x5 +4= 0
dx
du 4
= − 5
dx x
3(ii) du 4
[4] = − 5
dx x
Qn Solution
Integrating with respect to x on both sides of the equation,
4
u= ∫ − 5 dx
x
∫ −4 x
−5
= dx
= x −4 + c
y
y= ux3 ⇒ u =
x3
y
= 3
x −4 + c
x
y x −1 + cx3
=
When x = 1 , y = 3,
c=2
∴ y = x −1 + 2 x 3
Qn Solution
4(i) ac is the length of projection of c onto a
[1]
OR
ac is the length of projection of OC onto OA .
4(ii) ( 2a − b )( 2a − b ) = 4(aa) − 2(ab) − 2(ba) + (bb)
[3] 2 2
=4 a − 4(ab) + b ( ba =ab)
4(1) − 4 a b cos 60 + (2) 2
= 2 o
1
= 4 − 4(1)(2) + 4 = 4.
2
( 2a − b )( 2a − b ) =
2
2a − b = 4 ⇒ 2a − b = 2.
4(iii) By Ratio Theorem,
[1] b + 2a
c= .
3
4(iv) ac
cos ∠AOC =
[3] a c
b + 2a
a
3
= [from (iii)]
a c
1 ab + 2(12 ) 2
= [since a=
a a= 12 ]
3 c
1 ab + 2
= .
3 c
bc
cos ∠COB =
b c
b + 2a
b
3
= [from (iii)]
b c
1 22 + 2(ab) 2
= [since b=
b b= 22 ]
3 2c
1 2 + ab
= = cos ∠AOC.
3 c
Therefore line OC bisects the angle AOB.
Qn Solution
5(i) dx
x = tan θ ⇒ = sec 2 θ
[4] dθ
1 1
∫ x 2 + 1 dx = ∫ tan 2 θ + 1 ( sec θ ) dθ
2
1
=∫
sec θ
( sec2 θ ) dθ
= ∫ sec θ dθ
= ln sec θ + tan θ + c
= ln x2 + 1 + x + c
Alternatively,
1 + tan 2 θ =
sec 2 θ ⇒ sec θ =1 + x 2 .
5(ii) 1
=
[4] y −1
( x − 1)
2
1
=y2 −1
( x − 1)
2
1
( x − 1)
2
= 2
y +1
1
x − 1 =±
y2 +1
1
1−
x= ( x < 1)
y2 +1
Volume of solid
1
2 1
⌠ 3 1 ⌠ 3 2 1
=π 1 − dy =π 1 − + 2 dy
y 2
+ 1 ⌡ y 2
+ 1 y + 1
⌡0 0
O x
2
1 1
= b ( x − a) ⇒ b2 ( x − a )
2
=
a−x a−x
2
1
⇒ =( x − a ) ( a − x ) =( x − a )
2 2 4
b
1
⇒ = ( x − a ) (since b > 0)
2
b
1
⇒ x =a± .
b
1
Since x > a, x= a + .
b
6(iii) From the sketch in part (i),
[2] 1
x < a or a < x < a +
b
OR
1
x<a+ , x≠a
b
Qn Solution
7(i) un = a n +1
− ( n + 1)
a
[2]
u1 =0 ⇒ a 2 − 2a =0 ⇒ a 2 =2a … (*)
Method 1:
u3 = a 4 − 4a = ( a 2 ) − 4a
2
= (2 ) a 2
− 4a [from (*)]
= (2 ) 2 a
− 4a = 4a − 4a = 0.
Method 2:
u3 = a 4 − 4a = ( a 2 ) − ( 22 )
2 a
= (a ) − (2 )
2 2 a 2
( a − 2 )( a + 2 )
= 2 a 2 a
Qn Solution
n n
∑=
u ∑ 2 − ( r + 1)
r +1 2
=
r
r 1= r 1
n n
∑ 2r +1 − ∑ ( r + 1)
2
=
=r 1=r 1
n n
= ∑2 r +1
− ∑ ( r 2 + 2r + 1)
=r 1=r 1
n
n n n
=r 1
= ∑2 r +1
− ∑ r 2 + 2∑ r + ∑ 1
= r 1 =r 1 =r 1
4 ( 2n − 1) n n
= − ( n + 1)( 2n + 1) + 2 ( n + 1) + n
2 −1 6 2
n
= 4 ( 2n − 1) − ( n + 1)( 2n + 1) − n(n + 1) − n
6
n
OR 4 ( 2n − 1) − ( n + 1)( 2n + 1) − n 2 − 2n
6
n
OR 4 ( 2n − 1) − ( n + 1)( 2n + 1) − n(n + 2)
6
∑= ∑ 2 − ( r + 1)
r +1 2
ur
=r 1=r 1
n n
∑2 − ∑ ( r + 1)
r +1 2
=
=r 1=r 1
n n +1
=r 1=
=
r 2
∑ 2r × 2 − ∑ r 2
n
n +1
=2∑ 2r − ∑ r 2 − 12
= r 1= r 1
2 ( 2n − 1) n + 1
= 2 − ( n + 1 + 1) ( 2 ( n + 1) + 1) − 1
2 − 1 6
1
= 4 ( 2n − 1) − ( n + 1)( n + 2 )( 2n + 3) + 1
6
Qn Solution
7(iii) 9
[2] ∑ (v
r =1
r +1 − vr ) =v2 − v1
+ v3 − v2
+ ...
+ v9 − v8
+ v10 − v9
= v10 − v1
10
∑u
r =1
r = 3587. [from (ii) or from graphing calculator]
3587
Hence, v10 − v1 =
⇒ v10= 3587 + v=
1 3587 + u1 [since v=
1 u1 (given)]
= 3587 + [21+1 − (1 + 1) 2 ] (since =
⇒ v10 a 2)
⇒ v=
10 3587 +=
0 3587.
Qn Solution
8(i) y
[2]
y =1
O x
x=2
8(ii) x =+cot t 2 y= sec t
[3] dx dy
= − cos ec 2t =sec t tan t
dt dt
dy sec t tan t
=
dx − cos ec 2t
1 sin t
cos t cos t
=
1
− 2
sin t
sin 3 t
= −
cos 2 t
π
Since − < t < 0 , sin 3 t < 0, cos 2 t > 0
2
dy
Therefore > 0 , C is increasing
dx
8(iii) Method 1
Qn Solution
[2] Using GC,
π dy
At t = − , x= 1, y =1.4142, =0.70711 ,
4 dx
−1
Gradient of normal = −1.4142
0.70711
Equation of normal
y − 1.4142 = −1.4142 ( x − 1)
−1.4142 x + 2.8284
y=
−1.41x + 2.83 (3s.f.)
y=
-
Method 2
π
sin 3 −
π π dy 4 =1
At t =− , x= 1, y = sec = 2, =
− ,
4 4 dx 2 π 2
cos −
4
1
Gradient of normal − − 2
=
1
2
Equation of normal
y− 2 = − 2 ( x − 1)
y= − 2x + 2 2
8(iv) Midpoint R
[3] ( cot p + 2 ) − 2 sec p
= ,
2 2
cot p sec p
= ,
2 2
cot p sec p
= x = y
2 2
1
=tan p = sec p 2 y
2x
Method 1
Using trigonometric identity,
tan 2 p + 1 =sec 2 p
2
1
(2y)
2
+1 =
2x
1
4=y2 +1
4x2
-------------------------------------------------------------------------
Qn Solution
Method 2
1
tan p =
2x
Using the right angle triangle,
1
= 2y
2x
2
4x +1
4x2 + 1
y=
4x
-------------------------------------------------------------------------
Method 3
1
cos p =
2y
Using the right angle triangle,
1
tan p =
2x
1
= 2x
4 y2 −1
1
2
= 4x2
4 y −1
Qn Solution
9(a) For w = 1 − 3 i :
(i)
( 3)
2
[4] 1 − 3 i =12 +
w= 2
=
( w ) arg 1 −
arg= ( 3 i)
3 1
=− tan −1 =− π.
1 3
3 3
For z
= 2 cos π − i sin π :
4 4
3 3 3 3
z = 2 cos π − i sin π = 2 cos − π +i sin − π
4 4 4 4
3
Therefore z = 2 and arg ( z ) = − π .
4
Method 1
2
w= z* w =
2
z 22 = 2 4 2 ( )
Qn Solution
( w z *) arg ( w ) + arg ( z *)
arg = 2 2
= 2 arg ( w ) − arg ( z )
1 3 1
= 2 − π − − π = π.
3 4 12
1 1
Therefore,
= w2 z* 4 2 cos π + i sin π .
12 12
Method 2
π 3π 3π
− i − i i
w = 2e 3
, z
= 2e 4
z*
⇒= 2e 4
2
2
−π i 3π
i
w z* = 2e 3 2e 4
2π 3π
− i i
= 4e 3
2e 4
π
i
= 4 2 e12
1 1
= w2 z* 4 2 cos π + i sin π
12 12
9(a) Method 1
(ii) n nπ nπ
[2] w= 2n cos − + i sin −
3 3
( )
For Re wn = 0 ,
nπ
Re ( w =
) 2n n
cos − = 0
3
nπ
cos − = 0
3
nπ 3π π π 3π
− = ..., − , − , , ,...
3 2 2 2 2
nπ ( 2k + 1) π
=− , where k ∈
3 2
3 ( 2k + 1)
n= −
2
3 ( 2k + 1)
Since 3 ( 2k + 1) is odd for all k ∈ , is never an integer. Thus there is
2
no integer value of n such that the real part of wn is zero.
---------------------------------------------------------------------
Method 2
For the real part of wn to be zero, this means wn is purely imaginary.
Qn Solution
5π 3π π π 3π 5π
arg ( wn ) =..., − , − , − , , , ,
2 2 2 2 2 2
π
= ( 2k + 1) , where k ∈
2
n
Since arg ( wn ) = n arg ( w ) = − π ,
3
n π
− π = ( 2k + 1)
3 2
n 2k + 1
− =
3 2
3 ( 2k + 1)
n= −
2
3 ( 2k + 1)
Since 3 ( 2k + 1) is odd for all k ∈ , is never an integer. Thus there is
2
no integer value of n such that the real part of wn is zero.
9(b) 3 z 3 + 13 z 2 + 20 z + 14 =
0
(i) Since all coefficients of the equation are real and −1 + i is a root, −1 − i is another
[4] root.
A quadratic factor:
z − ( −1 + i ) z − ( −1 − i ) = [ z + 1 − i ][ z + 1 + i ]
= ( z + 1) − i ( z + 1) + i
=( z + 1) − i 2
2
= z 2 + 2 z + 1 − ( −1)
= z2 + 2z + 2
⇒ 3 z 3 + 13 z 2 + 20 z + 14 = (z 2
+ 2 z + 2 ) ( az + b )
Method 1 Method 2
Comparing z 3 terms: 3z + 7
2 3 2
a=3 z + 2 z + 2 3 z + 13 z + 20 z + 14
− ( 3z 3 + 6 z 2 + 6 z )
Comparing constant terms:
7z 2 + 14 z + 14
2b = 14
− ( 7z 2 + 14 z + 14 )
⇒b= 7
0
7
We have, 3 z 3 + 13 z 2 + 20 z + 14 = (z 2
+ 2 z + 2 ) ( 3 z + 7 ) . 3 z + 7 =0 ⇒ z =− .
3
7
Therefore, the other roots are −1 − i and − .
3
9(b) 3 2
Given w + 13w + 60 w + 126 = 0
(ii) Divide 9 throughout:
[2]
Qn Solution
1 3 13 2 60 126
w + w + w+ = 0
9 9 9 9
1 3 13 2 20
w + w + w + 14 =0
9 9 3
3 2
1 1 1
3 w + 13 w + 20 w + 14 =
0
3 3 3
1
So, z in 3 z 3 + 13 z 2 + 20 z + 14 has been replaced with w.
3
7
z =−1 + i, z =−1 − i, z =−
3
1 1 1 7
w =−1 + i, w =−1 − i, w =−
3 3 3 3
Therefore, w =−3 + 3i, w =−3 − 3i, w =−7 .
Qn Solution
10(i) dq
[2] To find maximum q, = 0 , i.e. I = 0 .
dt
q
0+ = V
C
q = VC
10(ii) q
[2] RI + = V
C
Differentiate with respect to t,
dI 1 d q d V
R + =
dt C dt dt
dV
If V is a constant, i.e. =0
dt
dI 1
R + (I ) = 0
dt C
dI I dq
R = + 0, since
= I
dt C dt
Qn Solution
10(iii) dI I
[5] R + = 0
dt C
dI I
= −
dt RC
1 1
∫ I dI = ∫ − RC dt
1
ln I = − t+d
RC
1 1
− t +d − t
=I e= e RC
e
RC + d
1
− t
I = Ae RC
V
When
= t 0,=I
R
V
A=
R
1
V − RC t
∴I = e
R
10(iv) I
[2]
O t
10(v) As t → ∞ , I → 0 .
[1]
In the long run, the current in the circuit tends to/approaches 0 amp.
Qn Solution
11( Amount of money Ali paid at the end of 3 years
a) 36
= 2 ( 200 ) + ( 36 − 1)(10 )
[2] 2
= 13500
Amount Ali owes the bank at the end of 3 years
= 50000 − 13500
= 36500
11( At the end of 1 month, amount owed
=b) 1.003 ( 36500 ) − 900
(i)
= 35709.50
Qn Solution
[2]
At the end of 2 months, amount owed
= 1.003 ( 35709.50 ) − 900
= 34916.6285
… … …
n 1.003n ( 36500 ) − 1.003n −1 ( 900 )
−1.003n − 2 ( 900 ) − ... − 900
Using GC,
n 1.003n ( 36500 ) − 300000 (1.003n − 1)
43 276.54
44 −622.6
45 −1524
Ali takes 44 months to pay off his study loan, i.e. he pays off his study loan in August
2027.
11( Method 1:
b) Since Ali pays $ (1.003 × 276.54 ) in the last month, total interest Ali paid
(iii)
=43 × 900 + (1.003 × 276.54 ) − 36500
[2]
= 2477.37 (nearest cent)
Qn Solution
Method 2:
Since Ali pays $276.54 in the last month, total amount he paid
= 13500 + 43 × 900 + (1.003 × 276.54 )
= 52477.37
Total amount of interest Ali paid
= 52477.37 − 50000
= 2477.37 (nearest cent)
11( Let the amount that Ali pays per month upon graduation be $x.
v) 1.00336 − 1
[3] 1.00336 ( 36500 ) − x ≤0
1.003 − 1
40656.16902 − 37.956 x ≤ 0
x ≥ 1071.14
Ali needs to pay $1072 per month.